Effect of the intensification of cropping sequences on soil organic carbon and its stratification ratio in contrasting environments - Crespo, Cecilia; Wyngaard, Nicolás; Sainz Rozas, Hernan Rene; Studdert, Guillermo; Barroco, Mirian; Gudelj, Vicente Jorge; Barbagelata, Pedro Anibal; Barbieri, Pablo (Elsevier, 2021)
In environments where continuous agriculture leads to soil organic carbon (SOC) depletion, intensification practices (i.e. polyculture, cover crops (CC), and crop fertilization) have been suggested as strategies to improve crop residue inputs which, in turn, can increase SOC storage. However, SOC dynamics are regulated by a complex interplay of climatic and soil conditions. The objective of our study was to assess how intensification practices affect SOC, particulate organic carbon (POC) and SOC stratification ratio (SRSOC) as compared to soybean [Glycine max (L.) Merr.] monoculture, in soils with contrasting soil properties and climate. The experiment was carried out in four long term experiments (>10 yr) located in areas with contrasting environments. The surface soil textures ranged from sandy-loam to silty-clay and clay-loam, initial SOC (0–20 cm) from 34.5 to 67.8 Mg ha−1, mean air temperature: 14.0–18.9 °C, annual precipitation: 719.8–886.1 mm. Five treatments were evaluated: soybean monoculture (SB), soybean monoculture fertilized with phosphorus (P) and sulfur (S) (SBPS), CC/PS-fertilized soybean (SBPS/CC), nitrogen (N)-fertilized CC/PS-fertilized soybean (SBPS/CCN) and NPS-fertilized crop rotation (ROTNPS). Intensification of crop sequences (SBPS/CC, SBPS/CCN and/or ROTNPS) increased SOC and POC at 0–5 cm and in SRSOC in most sites as compared to SB. All treatments showed SOC depletion as compared to the beginning of the experiment. However, the magnitude of SOC lost during 10 years was 26–65% lower when intensified crop sequences were applied as compared with SB. Carbon input and environment characteristics influenced the impact of intensification practices on the analyzed variables. However, this effect was mostly associated with the ratio between SOC at the beginning of the experiment and the SOC of pristine soil (degradation status). The intensification practices evaluated were not sufficient to reverse the tendency of agricultural soils to lose SOC, but they slowed the rate of this degradation process.